Prophylactic Closed Suction Drainage Is Irrelevant to Accelerated Rehabilitation after Open Reduction and Internal Fixation for Closed Distal Femur Fractures - Zhang, Jun‐zhe (Orthop Surg, 2020)
OBJECTIVE: To investigate whether closed suction drainage (CSD) is related to accelerated rehabilitation of patients after open reduction and internal fixation (ORIF) for closed distal femur fractures. METHODS: This study was a prospective, randomized controlled clinical trial. Between October 2018 and June 2020, 160 closed distal femur fracture patients who were prepared for ORIF were prospectively randomized into two groups: a CSD group with the mean age of 57.91 ± 14.38 years (32 [40%] men and 48 [60%] women) and a non‐CSD group with the mean age of 59.73 ± 17.55 years (27 [34%] men and 54 [66%] women). Wound visual analogue scale (VAS) pain scores, peri‐wound skin temperature, hematocrit (Hct), hemoglobin (Hb) concentrations, hidden blood loss (HBL), dressing change, period of wound oozing, postoperative blood transfusion, and length of postoperative hospital stay were recorded. Postoperative wound complications, namely wound infections, wound haematoma, wound dehiscence, erythema of wound, and lower limb deep vein thrombosis (DVT) were collected. All the patients were administrated by a single surgical team and followed up for 1 month after the ORIF. RESULTS: The patients without CSD were identified with lower peri‐wound skin temperature and wound VAS pain scores during the first three postoperative days (36.69 ± 0.33 vs 36.86 ± 0.38 °C, P = 0.002; 1.88 ± 0.82 vs 3.15 ± 1.15, P = 0.000). However, both the peri‐wound skin temperature and wound VAS pain scores did not differ significantly between the two groups on the fifth postoperative day. In addition, patients with CSD had a longer length of postoperative hospitalization time (11.45 ± 5.95 vs 9.78 ± 4.64 days, P = 0.049). There was no statistically significant difference between CSD and non‐CSD groups within 1 month after the ORIF regarding blood loss, period of wound oozing, and postoperative complications, such as incidence of wound infection, haematoma, erythema, dehiscence, and lower limb DVT. CONCLUSION: Prophylactic CSD after primary ORIF for closed distal femur fractures not only had no significant advantage to minimize blood loss and wound complications, but increased local inflammation and postoperative hospital stay, and thus we suggest that prophylactic CSD after primary ORIF for closed distal femur fractures is not recommended for optimized clinical pathways and accelerated recovery.